PROFIL GURU DAN TANTANGAN ZAMAN (Al'Adalah, 2002)
Globalization era, as a central issue of the society today and then, is a period of science and information that, according to Tilor (1999:208), is called as era of the emerge of learning society or knowledge society. Tertiary education, as an instituttion of scientific community in global society setting, is expected to be able to revonstruct it's vision, mission and social responsibility, in the current dimension as well. Thus, educational institution especially student-teacher education (FKIP) or Tarbiyah Department whose specification is to product teachers, according to Hasan Langgulung (1980:1991), should have three functions simultaneously, namely, preparing the young generation to play certain roles in society, transfer knowledge and values.